HEALTH AND PRODUCTIVITY GAINS FROM BETTER INDOOR ENVIRONMENTS AND THEIR RELATIONSHIP WITH BUILDING ENERGY EFFICIENCY - Fisk, William J. (Annual Review of Environment and Resources, 2000)
▪ Abstract Theoretical considerations and empirical data suggest that existing technologies and procedures can improve indoor environments in a manner that significantly increases productivity and health. The existing literature contains moderate to strong evidence that characteristics of buildings and indoor environments significantly influence rates of communicable respiratory illness, allergy and asthma symptoms, sick building symptoms, and worker performance. Whereas there is considerable uncertainty in the estimates of the magnitudes of productivity gains that may be obtained by providing better indoor environments, the projected gains are very large. For the United States, the estimated potential annual savings and productivity gains are 6 to 14 billion from reduced respiratory disease, 1 to 4 billion from reduced allergies and asthma, 10 to 30 billion from reduced sick building syndrome symptoms, and 20 to 160 billion from direct improvements in worker performance that are unrelated to health. Productivity gains that are quantified and demonstrated could serve as a strong stimulus for energy efficiency measures that simultaneously improve the indoor environment.
Keywords: productivity